Upaya Pembinaan Keagamaan Masyarakat Teja Timur Melalui Kambrat Senninan Berbasis Participatory Action Research (PAR) - Latifatul Mahbubah; Qurrotul Aini; Rafi’atun Najah Qomariyah (LP3M IAIFA Kediri, 2025)
Kambrat Senninan is a routine activity held every Monday, specifically for the women of Teja Timur Village, Pamekasan. It is led by a religious figure or kiyai and includes various activities, including reciting blessings, dhikr (remembrance of God), repentance prayers, congregational prayers, and religious lectures. The purpose of this community service is to provide religious guidance to mothers. Through this guidance, the mothers can relearn religious knowledge and expand their knowledge, which will ultimately improve the quality of their worship, given their varying educational backgrounds. This community service activity uses the Participatory Action Research (PAR) method which focuses on participation and collaboration with local community leaders. The results of the implementation indicate that the religious development activities, conducted through the Kambrat Senninan program in Teja Timur Village, Pamekasan, have been successful and achieved the desired results. The results of this development activity can be seen in the visible changes in the women during prayer and their increased devotion to prayer, dhikr, and supplication